2022
DOI: 10.17718/tojde.1137240
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Nursing Students’ Satisfaction With the Quality of Courses and Virtual Learning During the Covid-19 Pandemic in 2020-2021

Abstract: Education in medical sciences, including nursing, has encountered numerous challenges following the worldwide outbreak of coronavirus disease 2019 (COVID-19). Additionally, students’ satisfaction with the methods of instruction can be accompanied by improved learning outcomes. This study aimed to investigate the nursing students’ satisfaction with the quality of courses (SQC) and satisfaction with virtual learning (SVL) during the COVID-19 pandemic. This cross-sectional study was conducted at a nursing school … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 20 publications
0
15
1
6
Order By: Relevance
“…On the other hand, the current study contradicts findings with other studies, which showed students are dissatisfied with online learning [24]. Another study conducted in Iran showed that more than 88% of nursing students were satisfied with online learning [25]; furthermore, findings from the study conducted in Iran showed that universities were not completely successful in satisfying students in online learning [26].…”
Section: Discussioncontrasting
confidence: 97%
“…On the other hand, the current study contradicts findings with other studies, which showed students are dissatisfied with online learning [24]. Another study conducted in Iran showed that more than 88% of nursing students were satisfied with online learning [25]; furthermore, findings from the study conducted in Iran showed that universities were not completely successful in satisfying students in online learning [26].…”
Section: Discussioncontrasting
confidence: 97%
“…In all of these epidemics, high prevalence and high mortality rates caused a crisis (Chan et al, 2013; Tian et al, 2020). In fact, being drawn against an unknown and health-threatening situation can cause stress (Farsi et al, 2021). In contrast, knowing about the disease makes us less stressed on the face of it, but unfortunately, we did not know this at the beginning of the COVID-19 outbreak (Grech, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organisation has declared COVID-19 as a 'public health emergency of international concern' (Limcaoco et al, 2020). Two confirmed cases were reported in Qom, Iran, on 19 February 2020, and the government imposed suppression of people movement and lockdown in all the provinces after confirming new cases (Farsi et al, 2021). This condition led to the instability of many standard procedures worldwide, forcing nations into considerable burdens in socioeconomic, healthcare, political and educational domains (Farsi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the COVID pandemic has many economic, social, and cultural outcomes in all aspects of the life of the people worldwide, including education (21). Virtual training has received a lot of attention during the COVID pandemic (22,23). The use of radio, podcasts, television, and online education are the best ways of virtual learning (24).…”
Section: Introductionmentioning
confidence: 99%